Problems of design of non-oriented bottomhole assemblies of drill string - Юрич, Андрій Романович (Eastern-European Journal of Enterprise Technologies, 2013)
According to the results of the analysis of literary sources and publications in the research area, it was found that currently developed mathematical models of the study of the stress-strain state of BHA in the borehole do not fully take into account its operating conditions. In the design process, the BHA is considered as a beam, located in the straight or curvilinear borehole with certain imposed boundary conditions, which reflect the interaction of the elements of assembly and rock massif in static conditions. To ensure the high accuracy of drilling using non-oriented BHA it is necessary, at the design stage and directly in the drilling process, to have information on the actual conditions of the operation andinteraction of the assembly at the bottom-hole that is possible only when using the special measuring devices in the borehole design. The primary goal in solving difficult scientific-technological task is the improvement of the mathematical models of design by including the maximum number of various factors, which influence the stress-strain state of BHA in the borehole. The improved techniques must allow prompt estimation of the expediency of the assembly use based on the results of measuring the forces, occurring in the assembly. To estimate the stress-strain state and actual operating conditions of the assembly at the bottom-hole it is necessary to develop designs of special devices, which would be reliable and inexpensive to use